Quantitative changes in iris and retinal blood flow after femtosecond laser-assisted in situ keratomileusis and small-incision lenticule extraction - Cui, Lipu; Xue, Wenwen; Yao, Wenbo; Huang, Xinhui; Xue, Wen; Wang, Yulan; Li, Shanshan; Zhao, Liquan; Zou, Haidong (Frontiers in Medicine, 2022)
ABSTRACT Purpose: To investigate the quantitative changes in iris and retinal blood flow indices after femtosecond laser-assisted in situ keratomileusis (FS-LASIK) and small-incision lenticule extraction (SMILE). Methods: Seventy-nine patients who underwent FS-LASIK or SMILE were enrolled between July 2020 and September 2020. Participants were followed-up 1 day preoperatively and 1 week, 1 month, 3 months postperatively. Optical coherence tomography angiography (OCTA) was used to acquire and quantify the iris and retinal blood flow indices. Results: The iris vessel area density (VAD) and vessel skeleton density (VSD) decreased on postoperative day 1 but recovered on day 7. In both cases, the pupil diameter was positively associated with the postoperative iris blood flow indices (p=0.0013, p=0.0002). The retinal VAD and VSD in the superficial and deep capillary plexuses decreased after surgery and failed to recover after 90 days. The SMILE group showed significantly lower iris and retinal blood flow indices than the FS-LASIK group. For both procedures, axial length (p=0.0345, p=0.0499), spherical equivalence (p=0.0063, p=0.0070), and suction duration (p=0.0025, p=0.0130) were negatively correlated with the postoperative VAD and VSD. Conclusions: The SMILE and FS-LASIK procedures induced a short-term decrease in the iris and retinal blood flow indices, although patients finally showed full visual recovery. This phenomenon should be carefully considered, especially in patients prone to anterior segment lesions.